It’s alignment all the way down, but not all the way up: Speakers align on some features but not others within a dialogue - Ostrand, Rachel; Chodroff, Eleanor (Journal of phonetics, 2021)
•Speakers modulate their production to match their interlocutors’, called alignment.•We assess several individual features of syntactic and acoustic-phonetic alignment.•We also compute a holistic measure using machine learning on 323 individual phonetic features.•Speakers aligned on some but not all features within a linguistic level.•Speakers aligned at some linguistic levels but not others within the same dialogue. During conversation, speakers modulate characteristics of their production to match their interlocutors’ characteristics. This behavior is known as alignment. Speakers align at many linguistic levels, including the syntactic, lexical, and phonetic levels. As a result, alignment is often treated as a unitary phenomenon, in which evidence of alignment on one feature is cast as alignment of the entire linguistic level. This experiment investigates whether alignment can occur at some levels but not others, and on some features but not others, within a given dialogue. Participants interacted with two experimenters with highly contrasting acoustic-phonetic and syntactic profiles. The experimenters each described sets of pictures using a consistent acoustic-phonetic and syntactic profile; the participants then described new pictures to each experimenter individually. Alignment was measured as the degree to which subjects matched their current listener’s speech (vs. their non-listener’s) on each of several individual acoustic-phonetic and syntactic features. Additionally, a holistic measure of phonetic alignment was assessed using 323 acoustic-phonetic features analyzed jointly in a machine learning classifier. Although participants did not align on several individual spectral-phonetic or syntactic features, they did align on individual temporal-phonetic features and as measured by the holistic acoustic-phonetic profile. Thus, alignment can simultaneously occur at some levels but not others within a given dialogue, and is not a single phenomenon but rather a constellation of loosely-related effects. These findings suggest that the mechanism underlying alignment is not a primitive, automatic priming mechanism but rather guided by communicative or social factors.